La Petite Parade. - Sint-Vicentiuscollege, Eeklo; Brutin, Hugo (Eeklo : Sint-Vincentiuscollege - Sint-Leo-Instituut, 1987)
Baeyens, Martin R. ; Bilquin, Jean ; Bruyninckx, Rob ; Burssens, Jan ; Claus, Luc ; Copers, Leo ; Cuvelier, Werner ; De Clerck, Antoon ; de Mey, Gaston ; De Sauter, Willy ; De Smet, Yves ; Frimout, Cyr ; Marcase ; Landuyt, Octave ; Hoorne, Emiel ; Noel, Roger ; Raveel, Roger ; Rubens, Albert ; 't Kindt, Jacques ; Vandenberg, Philippe ; Vandewalle, Raf ; Verbeke, Ludo ; Van Severen, Dan ; Verstraete, Luc ; Willocx, André
biografie
La Petite Parade, Sint-Vincentiuscollege - Sint-Leo-Instituut, Eeklo, van 8 mei tot 24 mei 1987
Nederlands
boek